Clinical features and risk factors for developing varicella zoster virus dissemination following hematopoietic stem cell transplantation. Issue 2 (20th January 2014) - Umezawa, Y.; Kakihana, K.; Oshikawa, G.; Kobayashi, T.; Doki, N.; Sakamaki, H.; Ohashi, K.
Abstract Background We retrospectively analyzed 80 instances of varicella zoster virus (VZV) disease in 72 patients who underwent allogeneic hematopoietic stem cell transplantation (HSCT) and examined the clinical differences between localized and disseminated disease. Risk factors for developing VZV dissemination were also evaluated. Results Of the 80 instances, 54 instances were localized diseases and 26 were disseminated diseases. Patient characteristics did not differ significantly between the 2 groups, except for the first‐line therapy and the duration from symptom onset to treatment. In the disseminated group, intravenous acyclovir was used as the first‐line therapy more frequently, and more time elapsed before beginning antiviral therapy compared with the localized group. In multivariate analyses, the duration from symptom onset to treatment was identified as an independent risk factor that significantly affected the development of VZV dissemination. Gender, total body irradiation, and chronic graft‐versus‐host disease, of which the latter 2 factors were reported as risk factors for the development of VZV disease after HSCT, did not affect the development of VZV dissemination. Conclusion Our results suggest that VZV infection or reactivation may easily progress to viremia with delayed use of antiviral agents and may result in VZV dissemination in immunocompromised patients.